Acute rhino-orbito-cerebral mucormycosis in a patient with uncontrolled type I diabetes mellitus: a case report - Rohit; Sachin Khanduri; Khan, Zaara; Tariq Ahmad Imam; Ashok Gupta; Nadeem Alam; Namra Mahmood; Jaiswal, Vinima; Sana; Aastha Agrawal (International Journal of Research in Medical Sciences, 2024)
Rhino-orbito-cerebral mucormycosis (ROCM) is a severe and often fatal fungal infection that primarily affects immunocompromised individuals, especially those with diabetes mellitus. The fungi, primarily Rhizopus oryzae, exhibit angio-invasive properties leading to extensive tissue necrosis and vascular occlusion, contributing to high morbidity and mortality. Early diagnosis and prompt intervention are crucial for improving patient outcomes. We present the case of a 32-year-old female with uncontrolled type 1 diabetes mellitus who experienced progressive blackening of the skin on the right side of her face, weakness in both upper and lower limbs, swelling in the right orbital region, proptosis, and diminished vision in her right eye over 10 days. Diagnosis was made through physical examination and MRI findings. The patient underwent extensive debridement surgery and was treated with intravenous amphotericin B. MRI indicated complete mucosal thickening and air-fluid levels in the right maxillary sinus extending to the ethmoid, frontal, and sphenoid sinuses, and the "Black turbinate sign" was observed in the ipsilateral turbinates. Additional findings included right orbital cellulitis with endophthalmitis, optic neuritis, and an acute infarct in the right temporal lobe and ipsilateral lentiform nucleus. Successful surgical debridement and antifungal therapy followed the ROCM diagnosis. This case highlights the need for a high index of suspicion for ROCM in diabetic patients with facial and orbital symptoms, and emphasizes the necessity of early imaging and aggressive treatment to reduce the associated high risks.